Satellite laser ranging at ultra-high PRF of hundreds of kilohertz all day - Long, Mingliang; Zhang, Haifeng; Yu, Rong Zong; Wu, Zhibo; Qin, Si; Zhang, Zhongping (Frontiers in Physics, 2022)
Satellite laser ranging (SLR) had been worked at pulse repetition frequency (PRF) of some 10 Hz to 10 kHz, for ultra-high PRF of SLR has more advantages, it was new direction in the world.This paper reports an ultra-high PRF of 200kHz picosecond green laser with a single pulse energy of 80 μJ and a pulse width of 10 ps was used, it based on an aperture of 60cm SLR system in the Shanghai Astronomical Observatory. An alternate working mode of laser firing and gated pulse bursts was proposed to solve the problem of laser echoes interference by laser back scattered. In this mode, low-orbit to high-orbit and geostationary orbit satellites was measured in night day, and also for low-orbit and medium-orbit satellites in the daytime.The normal points (NPs) accuracy is ~30 μm for low-orbit of satellite and ~100 μm for high-orbit satellite, which provides an effective method for the development of ultra-high PRF and high-precision space target laser ranging.